ANALISIS STUDI FENOMENOLOGI MENGENAI DINAMIKA PSIKOLOGIS ANAK SEBAGAI KORBAN DISFUNGSI KELUARGA AKIBAT PERSELINGKUHAN ORANG TUA - Maulana, Topan; Muniruddin, Muniruddin (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The purpose of this study is to find out and understand the psychological dynamics of children who grow up in dysfunctional families due to parental infidelity. Using a qualitative approach and phenomenological methods, this study involved 3 siblings aged 22 years, 17 years and 13 years who had direct experience related to family dysfunction problems. The researcher as the first subject conducted in-depth, semi-structured interviews and non-participatory observations to understand the emotional and social experiences that arise due to the ongoing family conflict. The results showed that the three subjects experienced emotional distress, trust crises, feelings of loss of direction as well as disturbances in social relationships and self-development. However, each subject showed different responses and meanings according to their age and position in the family. The findings of this study are expected to be an important consideration in efforts to handle psychological more effectively to help children affected by similar family conflicts to rebuild their mental health and social adaptability in the future.